2013
DOI: 10.1155/2013/410609
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Bariatric Procedures versus Medical Therapy for Obese Patients with Type 2 Diabetes: Meta-Analysis of Randomized Controlled Trials

Abstract: Objective. To assess the effects of bariatric surgery versus medical therapy for type 2 diabetes mellitus. Methods. The Cochrane library, PubMed, Embase, Chinese biomedical literature database, and Wanfang database up to February 2012 were searched. The literature searches strategies contained terms (“diabetes∗”, “surg∗”, and “medic∗” were used), combined with the medical subject headings. Randomized controlled trails (RCTs) of frequently used bariatric surgery for obese patients with type 2 diabetes were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 23 publications
(72 reference statements)
0
15
0
6
Order By: Relevance
“…They were able to demonstrate superior results in the surgical group in terms of the reduction of fasting plasma glucose (FDG), glycosylated hemoglobin (HbA1c) and diabetes medications [44]. Three RCTs had been selected, accounting for 270 patients overall, 170 in the surgical and medical therapy group and 100 in the medical therapy group [10, 45, 46].…”
Section: Chapter 3: Specific Considerations and Indications For Surgementioning
confidence: 99%
“…They were able to demonstrate superior results in the surgical group in terms of the reduction of fasting plasma glucose (FDG), glycosylated hemoglobin (HbA1c) and diabetes medications [44]. Three RCTs had been selected, accounting for 270 patients overall, 170 in the surgical and medical therapy group and 100 in the medical therapy group [10, 45, 46].…”
Section: Chapter 3: Specific Considerations and Indications For Surgementioning
confidence: 99%
“…31,[68][69][70]164 A number of reviews reported on T2DM remission results from RCTs and included largely the same studies in their meta-analyses. Gloy et al 6 used meta-analysis to combine the results of four RCTs to give a relative risk of 5.3 (95% CI 1.8 to 15.8) for T2DM remission at 1-2 years of follow-up when comparing surgery with medical management, while a review by Guo et al 71 published in the same year included two RCTs to give an OR of 9.74 (95% CI 1.36 to 69.66). One further review, again published in 2013, employed meta-analysis to combine the results of eight RCTs to show a pooled estimate of 92% remission of T2DM after surgical intervention compared with 18% in control groups.…”
Section: Type 2 Diabetes Remissionmentioning
confidence: 99%
“…In 1995, Pories et al reported the long-term efficacy of bariatric surgery in achieving diabetes “remission” in 608 morbidly obese patients who underwent gastric bypass, with a 96.3 % follow-up rate over 14 years [19]. A later meta-analysis reported that DM was completely resolved in 76.8% of patients, however, a more recent analysis of randomized controlled trials indicates that figures may be lower [7, 20]. …”
Section: Effect Of Bariatric Surgery On Glycemic Controlmentioning
confidence: 99%